2015
DOI: 10.1016/j.jmpt.2015.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Lumbar-Hip Kinematics Between Trunk Flexion and Other Functional Tasks

Abstract: Strong correlations were only evident for the LL spine ROM between lifting and flexion; all other tasks afforded moderate or weak correlations. This study suggests that sagittal tasks use different lumbar-hip kinematics and place different demands on the lumbar spine and hip.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 18 publications
3
14
0
Order By: Relevance
“…The body of literature suggested that hip flexion angle contributed to rising from a seated position in healthy subjects ( 28 ). The results of this study showed that people with subacute stroke decreased maximal hip flexion angle during T 1 when compared with healthy adults before standing up from a seated position.…”
Section: Discussionmentioning
confidence: 99%
“…The body of literature suggested that hip flexion angle contributed to rising from a seated position in healthy subjects ( 28 ). The results of this study showed that people with subacute stroke decreased maximal hip flexion angle during T 1 when compared with healthy adults before standing up from a seated position.…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have examined lumbar kinematics during a single functional activity test,(Alqhtani et al, 2015; Shum et al, 2005a, b, 2007) very little has been reported on the consistency of aspects of the lumbar movement pattern across multiple functional activity tests. Marras et al reported people with LBP displayed increased cumulative spinal loading compared to BH people during a lifting task from varying heights and distances.…”
Section: Discussionmentioning
confidence: 99%
“…Studies where participants performed 2 or more movement tests primarily have focused on differences between (1) BH people and people with LBP, (2) LBP subgroups, or (3) patterns of movement at different movement speeds and object locations rather than the relationship between the movement during the tests . A recent study by Alqhtani et al reported an association between maximal upper ( r = 0.57) and lower ( r = 0.83) lumbar excursion during FWB and during a functional activity test separately . Different from the current study, however, the Alqhtani study included only BH males, there was no examination of lumbar excursion at increments of movement time, and the functional activity test involved picking up an object from the floor.…”
Section: Discussionmentioning
confidence: 74%